The Development of VAKISITE (Visual Auditory Kinesthetic Listening Website) For Listening Subject - Dwi Putri Hartiningsari; Alifa Zamza Rozalba (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2024)
This research was aimed at developing VAKISITE (Visual Auditory kinaesthetic Listening Website) to maximize students learning in the listening subject. The research used educational R&D Thus, this research used CAR (Classroom Action Research) research design to know the efficacy of the product in field testing step. The research procedures included needs analysis, studying education theories, developing the educational product, validating the product to experts, and field-testing. The research involved the second semester students of English Language Education Department of STKIP PGRI Trenggalek in 2022/2023 academic year as subject. The research instruments were field notes, questionnaires, and test. The field notes data was analysed in qualitative way, while questionnaire and test data was analysed in quantitative way.  The product has been developed through five steps of development.  Based  on  the  result  of  students'  needs, its score  was  80%, it’s showed that listening learning digital media were needed.  Meanwhile, the result of field testing the product of the students showed a percentage of 86%, 1723 scores of students’ feedback. It indicates that, the respondent agree that the product of this research was good and feasible to use as media in learning listening subject.